Z badań nad Biłgorajem. Weryfikacja i dopełnienie - Makarski , Władysław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article presents the state of research into the toponym Biłgoraj: initially incorrectly interpreted as a topographic name consisting of the segment Biel- “swamp” (>Ukrainian Bił-) and the morpheme -goraj “mountainous terrain”. Another interpretation of this toponym says that this name is memorial and physiographic in nature, with its first physiographic part coming from the local adjective *bieły (in general Polish biały “white”), shortened to Bieł- (>Ukrainian Bił-), referring to the first part of the name of the river *Bieła Łada < Biała Łada, which Biłgoraj is located on, and the second morpheme – the memorial one taken from the name of a nearby settlement Goraj, which was the seat of the ancestors of Adam Gorajski, the founder of Biłgoraj, a settlement also located on the river Biała Łada.